Parry's valuation and investment tables - Davidson, Alick W. (Routledge/Taylor and Francis Group, 2013)
First published in 1913, Richard Parry's Valuation and Investment Tables has since become an essential tool for students and professionals in the study and practice of valuation and appraisal. The book provides a comprehensive set of some 30 different valuation and investment tables in one volume. In practice today, calculations are required for a variety of purposes which often justify more than one approach. With this in mind, Internal Rates of Return tables have been retained in a modified form. Using these tables, both growth and non-growth scenarios can be analysed for a more detailed app.